Neighborhood Satisfaction and Colorectal Cancer Screening in a Community Sample of African Americans - Halbert, Chanita Hughes (J Community Health, 2016)
Social determinants are important to cancer screening among African Americans. To evaluate the association between social determinants (e.g., psychological characteristics, perceived social environment, cultural beliefs such as present temporal orientation) and colorectal cancer (CRC) screening among African Americans. African American adults (n = 262) ages 50–75 completed a telephone interview. Multivariate logistic regression analysis was used to identify factors having significant independent associations with CRC screening. Only 57 % of respondents reported having CRC screening. The likelihood of screening increased with greater neighborhood satisfaction (OR = 1.38, 95 % CI = 1.01, 1.90, p = 0.04), older age (OR = 1.75, 95 % CI = 1.24, 2.48, p = 0.002), greater self-efficacy (OR = 2.73, 95 % CI = 1.40, 5.35, p = 0.003), and health care provider communication (OR = 10.78, 95 % CI = 4.85, 29.94, p = 0.0001). Community resources are important precursors to CRC screening and outcomes among African Americans. In addition to addressing psychological factors and patient– provider communication, efforts to ensure the availability of quality health care facilities that provide CRC screening in the neighborhoods where African Americans live are needed.